Pembangunan Media Pembelajaran Jelajah Antariksa Kelas IX Pada Sekolah Menengah Pertama Negeri 8 Pati Berbasis Multimedia Interaktif - Hariyanto . (SPEED - Sentra Penelitian Engineering dan Edukasi, 2017)
Abstract – Development of educational technology can not be removed with the development oftechnology in general. A variety of educational tools and modern educational facilities whichcontribute to the optimization of the learning process, both in everyday environments and atschool. Development of technology, especially information and communications technologyoffers many range of easiness in learning. In the process of learning, development of materialsor teaching materials can be through various means, one of which is the development ofteaching materials with a medium of learning.Currently teaching at the Junior High School 8 Pati limited educational facilitiesespecially on the subjects of Physics. Obviously with such limitations, sometimes still causeproblems. Most of the problems that arise in terms of understanding the material presented andthe limitations of practical tools Physics subjects. Thus, thus to assist the delivery of messagesSpace Exploration material is necessary to a medium of learning physics, and is expected toaddress existing problems. Of this research is expected to provide facilities in theimplementation of teaching and learning activities in subjects of Physics.Keyword : FisikaAbstrak – Perkembangan teknologi pendidikan tidak dapat dilepaskan dengan perkembangan teknologipada umumnya. Berbagai perangkat pendidikan dan sarana pendidikan yang modern turut mendukungoptimalisasi proses pembelajaran, baik di lingkungan sehari-hari maupun di sekolah. Perkembanganteknologi khususnya teknologi informasi dan komunikasi banyak menawarkan berbagai kemudahankemudahandalam pembelajaran. Dalam proses pembelajaran, pengembangan materi atau bahan ajardapat melalui berbagai cara, salah satunya adalah pengembangan bahan ajar dengan mediapembelajaran.Saat ini pembelajaran di SMP Negeri 8 Pati masih terbatas sarana dan prasaranapendidikan khusunya pada mata pelajaran Fisika. Tentunya dengan keterbatasan tersebut,terkadang masih menimbulkan berbagai permasalahan. Sebagian besar permasalahan yangtimbul yaitu dalam hal pemahaman materi yang disampaikan dan keterbatasan alat-alat praktikmata pelajaran Fisika. Maka, dengan demikian untuk membantu penyampaian pesan materiJelajah Antariksa ini diperlukan adanya media pembelajaran Fisika, dan diharapkan dapatmengatasi permasalahan yang ada. Dari penelitian ini diharapkan agar memberikan kemudahandalam pelaksanaan kegiatan belajar mengajar dalam mata pelajaran Fisika.Kata kunci/Key word : Media pembelajaran, Fisika